2007
DOI: 10.1111/j.1475-1313.2007.00483.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of community optometrists to smoking cessation: an untapped opportunity overlooked?

Abstract: Aim: To assess community optometristsÕ attitudes and current behaviour regarding provision of smoking cessation advice in their practice. Methods: A self-completion postal questionnaire was sent to community optometrists in north-west England identified from the General Optical Council's practice lists. Results: Of 709 optometrists identified, 71.8% (509/709) returned the completed questionnaire. Few community optometrists routinely asked about smoking habits: only 6.2% (95% CI: 4.1-8.3) (n ¼ 31) at new patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 15 publications
0
40
3
Order By: Relevance
“…However, only a third of respondents in the current survey reported that they regularly took a smoking history in new patients and a similar number were proactive in advising on smoking cessation. Previous studies that have investigated the attitudes and practice of optometrists in this area have reported similar findings [30,31]. These studies also identified a number of barriers to routinely addressing a patient’s smoking behaviour including time constraints and a perceived need for further training in this area [31].…”
Section: Discussionmentioning
confidence: 59%
“…However, only a third of respondents in the current survey reported that they regularly took a smoking history in new patients and a similar number were proactive in advising on smoking cessation. Previous studies that have investigated the attitudes and practice of optometrists in this area have reported similar findings [30,31]. These studies also identified a number of barriers to routinely addressing a patient’s smoking behaviour including time constraints and a perceived need for further training in this area [31].…”
Section: Discussionmentioning
confidence: 59%
“…16 Eyecare practitioners, particularly high street optometrists, should also consider asking their adolescent patients whether they smoke, and to provide advice on quitting to smokers. Currently this opportunity is untapped, 17 and there are opportunities for ophthalmologists to improve their practice on smoking advice. 18 Our study adds weight to targeting teenagers, with the novel message ''smoking causes blindness'''…”
Section: Discussionmentioning
confidence: 99%
“…18 Similar findings were observed among community optometrists in the United Kingdom. 19 Hence, eyecare professionals can potentially have a greater role in the provision of targeted smoking cessation support for eye patients in routine ophthalmic and optometric practice. 20 This can be achieved through reducing perceived barriers by training eyecare professionals in providing an effective, brief intervention that is readily received by patients, as well as providing resources and materials to practitioners.…”
mentioning
confidence: 99%